Inversion of square matrices in processors with limited calculation abilities - Janiszowski, Krzysztof B. (Zielona Góra: Uniwersytet Zielonogórski)
An iterative inversion algorithm for a class of square matrices is derived and tested. The inverted matrix can be defined over both real and complex fields. This algorithm is based only on the operations of addition and multiplication.
Keywords: exponential matrix series; matrix inversion; neuro-processors